A glimpse of horizontal directional drilling productivity factors - Salleh, M.N.; Azam Haron, N.; Mohd Shafri, H.Z.; Abdullah, A.A.; Ahmad, N.F. (2018)
Horizontal Directional Drilling (HDD) is a trenchless technology provides an installation alternative that oﬀers a lot of beneﬁt compared to traditional open-cut method. It's called HDD because its steering ability to avoid existing utilities or other obstacles either horizontally, vertically and even pulled back where she got its name. HDD was developed in California in the 1970s and was introduced in Europe in 1986. Since year 1992 up to 2016 there are about 40 thousand unit HDD machine were sold worldwide. Contractors, consultants, municipalities and decision makers are always in diﬃculties to determine the installation cost and the duration required when using the HDD method due to the presence of many qualitative factors. Understanding the HDD productivity factors will assist the stakeholders to overcome this matter. The aims of this study are to identify the existing HDD productivity factors, identify the factors that aﬀect HDD productivity, identify the current tools that are used by current researcher, and identify the open problems and areas related to HDD productivity for improvement. Systematic Literature Review (SLR) was carried to previous related papers retrieved by a manual search, critically analysed and discussed. Researches regarding HDD productivity conducted by previous researchers were compared and discussed. The studies involved journal articles, conference papers, books, guidelines and etc. Consequently, these previous experiences and models can assist the contractors, consultants, municipalities and decision makers in preparing their costing and scheduling. The lacking factors on HDD productivity factors were highlighted and suggested for futre studies.